Preferred position of visual displays relative to the eyes: A field study of visual strain and... - Jaschinski W; Heuer H; Kylian H (Ergonomics)
At office workplaces equipped with visual display units (VDU) that were adjustable to various positions relative to the eyes short and long viewing distances from the eyes to the screen were imposed (mean value of about 63 and 92 cm) at two levels of screen height so that the visual target was either at eye level or 18 cm below, on the average. The change from far to near viewing distance produced a larger increase in eyestrain when the VDUs were at eye level. High screens resulted in greater eyestrain than low screens, as shown by correlations over subjects. When operators were free to adjust the most comfortable screen position, the group of 22 participants preferred viewing distances between 60 and 100 cm and vertical inclination of gaze direction between horizontal and -16 degrees downwards. However, within most subjects the range of preferred screen positions was much smaller. Between 3 days during a 1-month period the test-retest correlations of the preferred screen positions were highly significant, both for viewing distance and vertical gaze inclination. When operators were forced to work at a shorter distance than their preferred viewing distance they reported more visual strain. Thus, operators appear to prefer an individual adjustment of the screen relative to the eyes in order to avoid visual strain and discomfort at VDU work.